KEPENTINGAN FILIPINA MENERAPKAN KEBIJAKAN SPECIAL SAFEGUARD (SSG) TERHADAP IMPOR KOPI INSTAN DARI PT. MAYORA INDAH TBK PADA TAHUN 2018 - Anggraini, Nana; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study discusses the interests of the Philippines in implementing security measures against the import of instant coffee from PT. Mayora Indah Tbk Indonesia in 2018. The Philippines implemented a Safeguard policy in the form of a tariff increase, because instant coffee products from Indonesia dominate the Philippine market, resulting in threats to local farmers and domestic products. This research uses the perspective of mercantilism and the level of analysis of the nation state supported by the theory of national interests. This research is a qualitative research with descriptive analysis method that describes and solves a problem that is happening. This research states that it is in the Philippines' interest to implement a safeguard policy to protect local farmers and domestic products from the threat of loss, so that Indonesia lobbies the Philippines to normalize imports of instant coffee from the Mayora Group.